Genome-Wide Associations Between Human Genotypes and Mycobacterium tuberculosis Clades Causing Disease - Pitts, Stephanie Julia (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019